ABOUT THE LABORATORY DIAGNOSTICS OF SEVERE ACUTE RESPIRATORY SYNDROME AT PRIMORSKIJ TERRITORY - A. V. Allenov (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
The difficulties of SARS laboratory diagnosis, which took place at Primorski Territory during first months of this dangerous infection epidemic are shown.